Vibration-intensity prediction of underwater blasting based on grey relational analysis and dimension theory. (March 2020) - Wang, Z X; Gu, W B; Zhao, S T; Yu, L F; P C,; Xu, Jinglin
Abstract: In addition to the distance from the blasting center and the charge amount, the influence of the water depth of the blasting zone and the difference in elevation between the measuring points are non-negligible for the vibration intensity of underwater blasting. Hence, the conventional Sadov's formula is no longer fully applicable for the vibration-intensity prediction of underwater blasting. Combined with the vibration data of underwater blasting projects, a grey relational analysis of the influencing factors for blasting-vibration intensity has been conducted. The obtained order of the influence degree, from high to low, is the charge amount, elevation of the measuring point, water depth of the blasting zone, and the distance from blasting center. A formula for vibration-intensity prediction that comprehensively considers the influencing factors was derived from dimension theory; this formula is similar to Sadov's formula. The comparison of the two prediction results showed that the average error of the formula considering the water depth of the blasting zone and the difference in elevation was below 10%. This showed a significant improvement in the prediction accuracy, compared with the Sadov's formula, indicating that this derived formula is applicable for the vibration-intensity prediction of underwater blasting on land measuring points.